2011
DOI: 10.1109/tvcg.2010.82
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Hotspots—A Predictive Analytics Approach

Abstract: Current visual analytics systems provide users with the means to explore trends in their data. Linked views and interactive displays provide insight into correlations among people, events, and places in space and time. Analysts search for events of interest through statistical tools linked to visual displays, drill down into the data, and form hypotheses based upon the available information. However, current systems stop short of predicting events. In spatiotemporal data, analysts are searching for regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Data visualization is paramount to enhance the understanding of data. Maciejewski et al [9] have provided visual analytics systems to users to explore trends in their data. Linked views and interactive displays provide insight into correlations among people, events, and places in space and time.…”
Section: Related Workmentioning
confidence: 99%
“…Data visualization is paramount to enhance the understanding of data. Maciejewski et al [9] have provided visual analytics systems to users to explore trends in their data. Linked views and interactive displays provide insight into correlations among people, events, and places in space and time.…”
Section: Related Workmentioning
confidence: 99%
“…Maciejewski et al, [9], demonstrated the benefits of predictive visual analytics for forecasting syndromic hotspots. By linking a variety of data sources and models, they are able to enhance the hypothesis generation and exploration abilities of state epidemiologists.…”
Section: Litreature Reviewmentioning
confidence: 99%
“…A summary of some other methods that involve geospatial modeling can be found in [11,12]. Maciejewski et al [20] utilize the seasonal trend decomposition by loess smoothing for generating temporal predictions for modeling spatiotemporal healthcare events. They also use the kernel density estimation technique for creating probability distributions of patient locations for use in healthcare data.…”
Section: Predictive Visual Analyticsmentioning
confidence: 99%
“…To predict using the STL method, we apply the methodology described in [20], where the fitted valuesŶ = (ŷ 1 , ...,ŷ n ) generated using the loess operator in the STL decomposition step are considered to be a linear transformation of the input time series Y = (y 1 , ..., y n ). This is given byŷ i = ∑ n i=1 h i j y j ⇒Ŷ = HY , where H is the operator matrix whose (i, j)-th diagonal elements are given by h i, j .…”
Section: Time Series Prediction Using Seasonal-trend De-composition Bmentioning
confidence: 99%